Study of Tunable Plasmonic, Photoluminscence, and Nonlinear Optical Behavior of Ag Nanoclusters Embedded in a Glass Matrix for Multifunctional Applications. Issue 4 (28th December 2018) - Kumar, Promod; Mathpal, Mohan C.; Prakash, Jai; Hamad, Syed; Rao, Soma Venugopal; Viljoen, Bennie C.; Duvenhage, Mart‐Mari; Njoroge, Eric G.; Roos, Wiets D.; Swart, Hendrik C.
Abstract : Plasmonic based hybrid noble metal nanoclusters (NCs) have gained much interest in various technological applications such as optoelectronics, photonic devices and nonlinear media including biomedical applications due to their tunable optical properties. Here, Ag NCs are grown as embedded in glass using simple ion‐exchange process and effect of various parameter including post thermal treatment is studied on tunability of their optical behavior (plasmonic, optical nonlinearity, and photoluminescence properties) in view of their potential applications in nanophotonics devices and as nonlinear media. The tunable optical, structural and thermodynamic properties associated with the rapid growth and agglomeration of Ag NCs in the glass is also studied under the post thermal treatment process. The various techniques such as XRD, RBS, Z‐scan and UV‐vis, XPS, PL and TEM are used for characterizing ion exchanged samples. A blue shift of 15 nm is observed significantly in optical absorbance as a function of post thermal treatment. Open and closed aperture Z‐scan experiments show strong nonlinear absorption coefficients for the Ag NCs. The thermodynamic parameters such as enthalpy (ΔH), entropy (ΔS) and Gibbs energy (ΔG) for the nucleation and growth of the Ag NCs in the glass matrix are calculated at different temperatures with an activation energy of 59 kJ mol −1 obtained by the Arrhenius linear equation and a model is suggested. In addition, these Ag NCs embedded glasses exhibit good antimicrobial activities (against E. coli bacteria) with a change in antibacterial behavior at higher annealing temperature indicating their multifunctional applications. Abstract : Ag nanoclusters are grown as embedded in glass using a simple ion‐exchange process and the effect of various parameters including post thermal treatment is studied on the tunability of their optical behavior (plasmonic, optical nonlinearity, and photoluminescence properties) in view of their potential applications in nanophotonics devices and as nonlinear media.